Colorimetric textile sensor for the simultaneous detection of nh3 and hcl gases - Park, Young Ki; Oh, Hyun Ju; Bae, Jong Hyuk; Lim, Jee Young; Lee, Hee Dong; Hong, Seok Il; Son, Hyun Sik; Kim, Jong H.; Lim, Seung Ju; Lee, Woosung (Polymers, 2020)
For the immediate detection of strong gaseous alkalis and acids, colorimetric textile sensors based on halochromic dyes are highly valuable for monitoring gas leakages. To date, colorimetric textile sensors for dual-gas detection have usually been fabricated by electrospinning methods. Although nanofibrous sensors have excellent pH sensitivity, they are difficult to use commercially because of their low durability, low productivity, and high production costs. In this study, we introduce novel textile sensors with high pH sensitivity and durability via a facile and low-cost screen-printing method. To fabricate these textiles sensors, Dye 3 and RhYK dyes were both incorporated into a polyester fabric. The fabricated sensors exhibited high detection rates (<10 s) and distinctive color changes under alkaline or acidic conditions, even at low gas concentrations. Furthermore, the fabricated sensors showed an outstanding durability and reversibility after washing and drying and were confirmed to contain limited amounts of hazardous materials. Thus, our results show that the fabricated textile sensors could be used in safety apparel that changes its color in the presence of harmful gases.
Keywords: Acidic conditions; Electrospinning method; Fabricated sensors; Gas concentration; High detection rate; Polyester fabric; Screen printing methods; Simultaneous detection; Durability; Gas detection; PH sensitivity; Screen printing; Textile sensor